The influence of plasticizer on the mechanical, structural, thermal and strain recovery properties following stress-relaxation process of silk fibroin/ sodium alginate biocomposites for biomedical applications - Aksakal, Baki; Kaplan, Zehra; Turhan, Kadir (ELSEVIER, 2025)
The influence of plasticizer glycerol (GLY) on the mechanical, structural, and thermal properties of silk fibroin (SF)/sodium alginate (SA) biocomposite films was investigated in detail. As the SF/SA ratio increased up to 65%, the SF content significantly improved the Tensile strength (sigma T), Young's modulus (Ey) but reduced the elongation at break (epsilon b). To modify and enhance the elasticity and flexibility of the biocomposite films, the GLY as a plasticizer was used at different ratio from 20 to 50% for each SF/SA biocomposite films. Although the extensibility of the films was improved greatly with increasing GLY ratio, sigma T and Ey reduced significantly. The effect was observed more apparently for the GLY ratio starting from 35%. It was also shown that crystallinity index in the Amide I region increased as the SF/SA ratio increased to 65%. Increasing SF content improved the thermal stability of the SF/SA biocomposites. The XRD results showed that crystallinity was increased as SF/SA ratio increased. Stress-relaxation of SF/SA (30%) biocomposite films plasticized with GLY revealed that each kind of plasticized films showed a viscoelastic behavior and a fast relaxation in the first stage (1-2 min) of the processes and then continued slowly. The GLY increased the extensibility and elasticity limit of the SF/SA (30%) composite films. During the strain recovery processes, the plasticized composite films recovered completely in a quite shorter time than that of unplasticized films. It was observed higher the GLY content, the recovery times became shorter.
Keywords: Silk fibroin; Sodium alginate; Plasticizer; Elasticity; Stress-relaxation; Strain recovery; TRANSFORM INFRARED-SPECTROSCOPY; BOMBYX-MORI; PHYSICAL-PROPERTIES; FILMS; CRYSTALLINITY; DEGRADATION; SCAFFOLD; FIBERS; WATER; NANOPARTICLES; Engineering; Materials Science